Dos Palácios Cinematográficos aos Cinemões: deslocamentos da arquitetura sexopolítica no centro de São Paulo - Silva, Gabriel José Camarano da (Universidade Federal de São Carlos, 2025)
The research intends to comprehend, through the analysis of the "cinemões" ( how porn/adult movie theaters are known) that are found within downtown São Paulo, how the architecture of sex politics in the capital has (un)organized itself throughout this century, between the first decades of the 1900s (period of time in which the Picture Palaces were born) until present days. Considering the "marginalisation" of the centre ( and the relocation of not only the elite, but also the traditional cinemas, to the regions of the neighborhoods of Paulista and Jardins) and the radical and obscene changes of those built spaces, mostly between the decades of 1930 and 1950 as palaces that resembled the disciplinary ideals of the city. This research is interested in finding the meaning of this pornographic "inversion". In other words: how the unfolding of these architectural structures (and the streets that encompass them) can be noticed, and how they were planned to receive primarily a specific "black tie and pearl necklace" type of couple, in new architectures encompassed by "pornotopia", hookup spaces and the LGBT sociability.
From Picture Palaces to "Cinemões" (adult movie theaters): shifts in sexopolitical architecture in downtown São Paulo
Keywords: Palácio Cinematográfico; Cinema Pornô; Cinemão; Cinelândia Paulistana; Sexopolítica; Pornotopia; LGBTQ+; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA; 11. Cidades e Comunidades Sustentáveis